Mechanical and flexural performance of self compacting concrete with natural fiber - Kavitha, Sethuraman Muthusamy; G., Venkatesan; Avudaiappan, Siva; Saavedra Flores, Erick (Revista de la Construcción. Journal of Construction, 2020)
This paper investigates the effect of sisal fiber addition on fresh ,mechanical properties of self compacting concrete(SCC) and flexural performance of fiber reinforced RC beams made with mineral admixtures like Meta Kaolin (MK) and Fly Ash (FA)which is an industrial waste. The mixes were prepared by varying MK content from 5% to 15% with 5% increment with constant fly ash content of 30%. The results reveal that increasing the content of MK beyond 10% leads to reduction in strength. And also the negative influence of MK and fiber addition on workability performance was overcome by the addition of FA, super plasticizer and viscosity modifying agent (VMA). Based on the test results it is evidenced that FA and MK make use of mineral admixture in the production of SCC. It also clarifies that the addition of sisal fiber improves mechanical properties of concrete. The research work shows that the ultimate load of fiber reinforced RC beams was raised when compared to normal RC beams. The flexural toughness and ductility of concrete was found to increase appreciably when sisal fiber was added.